The Study of Hereditary Spastic Paraplegia-Causing Gene DDHD2 Using Cell Models - Mongeon, Kevin (Université d'Ottawa / University of Ottawa, 2018)
Hereditary spastic paraplegia type 54 is a rare autosomal recessive neurological gait disorder characterized by paraplegia, muscle spasticity, and intellectual disability. This length-dependent distal axonopathy is caused by mutations in the DDHD2 gene, which encodes the intracellular phospholipase A1 DDHD2. Little is known about the molecular function of the DDHD2 protein, especially in the context of HSP54. Thus, there is a need to further investigate its molecular functions and investigate the impact of DDHD2 deficiency in disease-relevant cells. Here, lipidomic profiling of dermal fibroblasts derived from three unrelated patients has revealed 19 glycerophosphoethanolamine species at differential levels in patients relative to unaffected controls. However, patient cells appear to have an unaffected Golgi apparatus morphology and lipid droplet formation, despite DDHD2’s proposed roles in these processes. To study the gene function in neuronal cells, I transdifferentiated the fibroblasts into induced neuronal precursor cells and found all the patient cells arrested in the G0/G1 phase of upon conversion. Given that these cell lines are unsustainable, I generated a stable knockdown cell line in the highly proliferative HEK293A to study the molecular biology of DDHD2. The knockdown cells had a reduced growth, were delayed in the G2/M phase of the cell cycle, and became multinucleated. I then treated the cells with antineoplastic compounds paclitaxel and nocodazole and found more knockdown cells in G0/G1 than controls, suggesting the possible occurrence of mitotic slippage. Lastly, I report a novel subcellular localization for DDHD2 at the microtubule organization center.
Keywords: Hereditary Spastic Paraplegia; DDHD2; Cell Model; Golgi; Lipid droplet; Lipidomics; Microtubules; Microtubule organization center; Cell cycle; Mitotic slippage; Induced neuronal precursor cells; Transdifferentiation; Genetics; Neuromuscular disease; Neurodegenerative; Gait disorder